The microbiome of deep-sea fish reveals new microbial species and a sparsity of antibiotic resistance genes. (1st January 2021) - Collins, Fergus W. J.; Walsh, Calum J.; Gomez-Sala, Beatriz; Guijarro-García, Elena; Stokes, David; Jakobsdóttir, Klara B.; Kristjánsson, Kristján; Burns, Finlay; Cotter, Paul D.; Rea, Mary C.; Hill, Colin; Ross, R. Paul
ABSTRACT: Adaptation to life in the deep-sea can be dramatic, with fish displaying behaviors and appearances unlike those seen in any other aquatic habitat. However, the extent of which adaptations may have developed at a microbial scale is not as clear. Shotgun metagenomic sequencing of the intestinal microbiome of 32 species of deep-sea fish from across the Atlantic Ocean revealed that many of the associated microbes differ extensively from those previously identified in reference databases. 111 individual metagenome-assembled genomes (MAGs) were constructed representing individual microbial species from the microbiomes of these fish, many of which are potentially novel bacterial taxa and provide a window into the microbial diversity in this underexplored environment. These MAGs also demonstrate how these microbes have adapted to deep-sea life by encoding a greater capacity for several cellular processes such as protein folding and DNA replication that can be inhibited by high pressure. Another intriguing feature was the almost complete lack of genes responsible for acquired resistance to known antibiotics in many of the samples. This highlights that deep-sea fish microbiomes may represent one of few animal-associated microbiomes with little influence from human activity. The ability of the microbes in these samples to bioluminesce is lower than expected given predictions that this trait has an important role in their life cycle at these depths. The study highlights the uniqueness, complexity and adaptation of microbial communities living in one of the largest and harshest environments on Earth.